Immediate lifting delivery - Giampietro, Alfonso (2015)
Submit to the consideration of our fellow members experience the immediate postpartum survey. We consider timely disclosure of this personal experience in our environment, because the same thing is done and abroad through publications in magazines and exhibitions in films.